Identification of quantitative trait nucleotides for grain quality in bread wheat under heat stress - Latief Bashir; Neeraj Budhlakoti; Anjan Kumar Pradhan; Divya Sharma; Antil Jain; Saman Saim Rehman; Vishal Kondal; Sherry R. Jacob; Rakesh Bhardwaj; Kiran Gaikwad; Dwijesh Chandra Mishra; Abhishek Pandey; et al. (Scientific Reports)
Abstract Heat stress is a critical factor affecting global wheat production and productivity. In this study, out of 500 studied germplasm lines, a diverse panel of 126 wheat genotypes grown under twelve distinct environmental conditions was analyzed. Using 35 K single-nucleotide polymorphism (SNP) genotyping assays and trait data on five biochemical parameters, including grain protein content (GPC), grain amylose content (GAC), grain total soluble sugars (TSS), grain iron (Fe), and zinc (Zn) content, six multi-locus GWAS (ML-GWAS) models were employed for association analysis. This revealed 67 stable quantitative trait nucleotides (QTNs) linked to grain quality parameters, explaining phenotypic variations ranging from 3 to 44.5% under heat stress conditions. By considering the results in consensus to at least three GWAS models and three locations, the final QTNs were reduced to 16, with 12 being novel findings. Notably, two novel markers, AX-94461119 (chromosome 2A) and AX-95220192 (chromosome 7D), associated with grain Fe and Zn, respectively, were validated through Kompetitive Allele Specific Polymerase Chain Reaction (KASP) approach. Candidate genes, including the P-loop-containing nucleoside triphosphate hydrolases (NTPases), Bowman-Birk type proteinase inhibitors (BBI), and the NPSN13 protein, were identified within associated genomic regions. These genes could serve as potential targets for enhancing quality traits and heat tolerance in future wheat improvement programs.